2008
DOI: 10.1103/physrevb.78.075426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface site on the spin state of first-row transition metals adsorbed on MgO: Embedded cluster model and hybrid density functional theory calculations

Abstract: The interaction of first-row transition-metal atoms with low-coordinated oxygen atoms and oxygen vacancies of the MgO surface at low coverage has been studied systematically using an embedded-cluster model approach and hybrid density functional theory calculations. It was found that the interaction with these defects is much stronger than with the regular sites but in general insufficient to change the number of unpaired electrons in the free metal atom. Nevertheless, the larger interaction at these sites redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…For weak interactions, the intraatomic exchange favors Hund’s rule as in the isolated atoms and the high-spin state is maintained, although the energy difference between the high- and low-spin states is reduced with respect to the atomic value . However, a stronger interaction with the underlying oxide surface results in bonding and antibonding orbitals with occupation of the lowest energy ones, concomitant electron pairing, and spin quenching. , For Pt on CeO 2 (111) we see that high- and low-spin states are nearly degenerate and, in addition, the high-spin state involves charge transfer from the metal to the surface with subsequent reduction of one Ce 4+ cation to Ce 3+ , a process which cannot occur in an nonreducible oxide such as MgO. , …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…For weak interactions, the intraatomic exchange favors Hund’s rule as in the isolated atoms and the high-spin state is maintained, although the energy difference between the high- and low-spin states is reduced with respect to the atomic value . However, a stronger interaction with the underlying oxide surface results in bonding and antibonding orbitals with occupation of the lowest energy ones, concomitant electron pairing, and spin quenching. , For Pt on CeO 2 (111) we see that high- and low-spin states are nearly degenerate and, in addition, the high-spin state involves charge transfer from the metal to the surface with subsequent reduction of one Ce 4+ cation to Ce 3+ , a process which cannot occur in an nonreducible oxide such as MgO. , …”
Section: Resultsmentioning
confidence: 87%
“…60 However, a stronger interaction with the underlying oxide surface results in bonding and antibonding orbitals with occupation of the lowest energy ones, concomitant electron pairing, and spin quenching. 61,62 For Pt on CeO 2 (111) we see that high-and low-spin states are nearly degenerate and, in addition, the high-spin state involves charge transfer from the metal to the surface with subsequent reduction of one Ce 4+ cation to Ce 3+ , a process which cannot occur in an nonreducible oxide such as MgO. 63,64 In the case of the closed-shell singlet state, two proper local minima are justified by the frequency analysis.…”
Section: Resultsmentioning
confidence: 94%
“…Florez et al considered the effects of adsorption on that atomic spin states of the adsorbed metals and found that although spin-state splittings were reduced, high-spin states were in general not quenched upon adsorption. 1047 Hinneman and Carter 1048 used the PBE density functional to study the adsorption of Y, Hf, and Pt on g-Al 2 O 3 (0001). They found that Y and Hf form strong ionic bonds at 3-fold hollow sites, whereas Pt bonds more weakly at an on-top site without appreciable charge transfer.…”
Section: Solidsmentioning
confidence: 99%
“…In some cases such as V, Ni, and Co, a change in the multiplicity of the ground state with respect to the free atom is observed. Ni is a special case, because the PW91 functional describes incorrectly its atomic electronic ground state. , To investigate whether a stronger interaction can completely quench the magnetic moment of the adsorbed atom, Florez et al studied the same systems using embedded cluster models and the hybrid B3LYP functional, but considering low-coordinated sites and adsorption at F centers as well . The interaction above low-coordinated anion sites and F s centers was found to be stronger than on the regular terrace O sites.…”
Section: Excited States Related To Adsorbates At Oxide Surfacesmentioning
confidence: 99%